2021
DOI: 10.1097/aog.0000000000004385
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Diagnostic Value of Genome-Wide Noninvasive Prenatal Testing in Multiple Gestations

Abstract: To evaluate the accuracy and diagnostic value of genome-wide noninvasive prenatal testing (NIPT) for the detection of fetal aneuploidies in multiple gestations, with a focus on dichorionic-diamniotic twin pregnancies. METHODS:We performed a retrospective cohort study including data from pregnant women with a twin or higher-order gestation who underwent genome-wide NIPT at one of the eight Belgian genetic centers between November 1, 2013, and March 1, 2020. Chorionicity and amnionicity were determined by ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…In this study, we found that NIPT has good screening performance for T21 and SCA in twin pregnancies. The sensitivity and specificity of NIPT for T21 were 100% and 99.9%, respectively, which are consistent with the results of singleton or other twin studies [ 12 14 ]. For SCA, NIPT has a different sensitivity and specificity according to the types of SCA in singleton pregnancies, and the PPV is between 21.4% and 90.9% [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we found that NIPT has good screening performance for T21 and SCA in twin pregnancies. The sensitivity and specificity of NIPT for T21 were 100% and 99.9%, respectively, which are consistent with the results of singleton or other twin studies [ 12 14 ]. For SCA, NIPT has a different sensitivity and specificity according to the types of SCA in singleton pregnancies, and the PPV is between 21.4% and 90.9% [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 89%
“…Four studies included only high risk pregnancies, 25–28 that is, advanced maternal age (>35 years at delivery), abnormal fetal findings on ultrasound examination, personal history of a child with aneuploidy, abnormal serum screening results, or a parent carrying a balanced Robertsonian translocation. Two studies included a mixed risk population, 23,24 and one included women of the general obstetric population 10 . One study described the chorionicity of the VTs and made a distinction between two types of VTs: type I with an additional empty GS and type II with a non‐viable embryo 27 .…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were retrospective observational cohort studies, 10,[23][24][25] and three were prospective observational cohort studies, [26][27][28] all published between 2018 and 2021. The cohort sizes ranged from 5 to 767 VT pregnancies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…51 Although based on small numbers, noninvasive prenatal testing (NIPT) appears to have similar accuracy as in singletons. 56 However, to exclude heterokaryotypic monochorionic twins, a positive NIPT is best confirmed by a dual amniocentesis, unless both twins show concordant anomalies on the first-trimester scan.…”
Section: Diagnosismentioning
confidence: 99%